2002
DOI: 10.1007/s00299-001-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated production of transgenic plants of Muscari armeniacum Leichtl. ex Bak.

Abstract: A system for the production of transgenic plants has been developed for the Liliaceous ornamental plant Muscari armeniacum Leichtl. ex Bak via Agrobacterium-mediated transformation of embryogenic cultures. Leaf-derived embryogenic cultures were co-cultivated with each of three A. tumefaciens strains, all of which harbored the binary vector carrying the neomycin phosphotransferase II (nptII), hygromycin phosphotransferase (hpt) and intron-containing β-glucuronidase (gus-intron) genes in the T-DNA region. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…In these cases, an improvement in the transient expression levels will not necessarily result in better stable transformation (Shen et al 1993;Ishida et al 1996;Maximova et al 1998). However, most studies have shown that conditions leading to enhanced transient expression do result in a higher number of transformed plants (Cao et al 1998;Kondo et al 2000;Niu et al 2000;Zhang et al 2000;Choi et al 2001;Trifonova et al 2001;Suzuki and Nakano 2002).…”
Section: Resultsmentioning
confidence: 98%
“…In these cases, an improvement in the transient expression levels will not necessarily result in better stable transformation (Shen et al 1993;Ishida et al 1996;Maximova et al 1998). However, most studies have shown that conditions leading to enhanced transient expression do result in a higher number of transformed plants (Cao et al 1998;Kondo et al 2000;Niu et al 2000;Zhang et al 2000;Choi et al 2001;Trifonova et al 2001;Suzuki and Nakano 2002).…”
Section: Resultsmentioning
confidence: 98%
“…Southern blot analysis has been the usual means to verify the transgenic nature and to determine the copy number of transgenes in plant genomes (Watad et al 1998;Suzuki et al 2001;Suzuki and Nakano 2002). As this technique requires relatively large amounts of genomic DNA, it is difficult to obtain a clear signal if the genome size of the subject plant is large.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al 2001;Suzuki and Nakano 2002) or regeneration medium (e.g. Watad et al 1998) was used for selecting transformed lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern hybridization was performed according to Suzuki and Nakano (2002). V. major genomic DNA (50 mg) was digested with either HindIII, XbaI, ScaI or SacI.…”
Section: Southern Hybridizationmentioning
confidence: 99%